EMISSION AND OXIDATION OF METHANE IN EQUISETUM FLUVIATILE STANDS GROWING ON ORGANIC SEDIMENT AND SAND BOTTOMS - Kankaala P.; Bergstrom I. (My University, 2004)
Methane emission and rhizospheric CH4 oxidation were studied in stands of Equisetum fluviatile, a common cryptogam in boreal lakes. The experiment was performed in mesocosms with organic sediment or sand bottoms under natural variation of temperature and light using the light-oxic - dark-anoxic chamber (LO/DA) technique. Net CH4 emission from the organic sediment during the growing season varied between 3.4 and 19.0 mg m-2 h-1, but from sand the net CH4 emission was only 3-10% of that measured from the organic sediment. In the organic sediment net CH4 emission was very significantly correlated with sediment temperature (r2 = 0.92). In the sand mesocosms the variation of net CH4 emission was better correlated with the shoot biomass than with sediment temperature variation during the growing season, indicating that methanogens were severely limited by substrate availability and were probably dependent on substrates produced by E. fluviatile. The proportion of the methane oxidized of the potential CH4 emission in summer did not differ significantly between the bottom types. The net CH4 emission during the growing season as a proportion of the seasonal maximum of the shoot biomass was significantly higher in the organic sediment mesocosms (6.5%) than in sand (1.7%). The high CH4 emissions observed from dense well-established E. fluviatile stands in the field appear to be more related to temperature-regulated turnover of detritus in the anaerobic sediment and less to CH4 oxidation and seasonal variation in plant growth dynamics
Keywords: BOREAL LAKE; CH4 EMISSION; CH4 OXIDATION; EMERGENT MACROPHYTES; EQUISETUM FLUVIATILE SEDIMENT QUALITY